2006
DOI: 10.1016/j.neuroimage.2005.11.047
|View full text |Cite
|
Sign up to set email alerts
|

Native and non-native reading of sentences: An fMRI experiment

Abstract: The processing of syntactic and semantic information in written sentences by native (L1) and non-native (L2) speakers was investigated in an fMRI experiment. This was done by means of a violation paradigm, in which participants read sentences containing either a syntactic, a semantic, or no violation. The results of this study were compared to those of a previous fMRI study, in which auditory sentence processing in L1 and L2 was investigated. The results indicate greater activation for L2 speakers as compared … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
47
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 95 publications
(57 citation statements)
references
References 73 publications
8
47
1
Order By: Relevance
“…This suggestion is akin to the evidence presented in Suh et al (2007: Figure 4), where the participants did not show differences in LIFG activity between sentences with central embedding compared to conjoined sentences of the same length. Rather than the absence of an increase for embedded sentences, the lack of a statistical difference appeared to be driven by similar increase in LIFG activity for conjoined sentences, which was higher than that for L1 processing (see also Rüschemeyer, Zysset & Friederici 2006, for regions showing increased activation for L2 vs. L1 sentence processing). Another possiblity for the absence of LIFG effects may lie with its purported role in the integration of semantic information during sentence processing (Friederici 2012;Hagoort 2014).…”
Section: Discussionmentioning
confidence: 91%
“…This suggestion is akin to the evidence presented in Suh et al (2007: Figure 4), where the participants did not show differences in LIFG activity between sentences with central embedding compared to conjoined sentences of the same length. Rather than the absence of an increase for embedded sentences, the lack of a statistical difference appeared to be driven by similar increase in LIFG activity for conjoined sentences, which was higher than that for L1 processing (see also Rüschemeyer, Zysset & Friederici 2006, for regions showing increased activation for L2 vs. L1 sentence processing). Another possiblity for the absence of LIFG effects may lie with its purported role in the integration of semantic information during sentence processing (Friederici 2012;Hagoort 2014).…”
Section: Discussionmentioning
confidence: 91%
“…It is unclear, though, whether L2 speakers display the same kind of embodiment effects as L1 speakers, as hardly any study has addressed this issue. A number of fMRI studies have looked into semantic processing in bilinguals (Chee, Hon, Lee, & Soon, 2001;Illes et al, 1999;Isel, Baumgaertner, Thrän, Meisel, & Büchel, 2010;Rüschemeyer, Zysset, & Friederici, 2006;Wartenburger et al, 2003). However, none of these systematically manipulated motor-relatedness, for example by including a contrast between motor and non-motor words or between different types of motor words, thus precluding any conclusions as to the embodied nature of L2 semantic representations.…”
Section: Introductionmentioning
confidence: 99%
“…In the violation detection task (Ni et al, 2000), semantic processing may terminate earlier in the incongruent condition than in the congruent condition due to a specific reading strategy (Huang et al, 2012;Zhu et al, 2009). Although activation in the LIFG has been reported in a wide range of tasks, including semantic congruency judgment (Constable et al, 2004;Rueschemeyer et al, 2006;Zhu et al, 2009), meaningfulness rating (Humphries et al, 2007), reading for comprehension (Hagoort et al, 2004;Tesink et al, 2009), comprehension probe test (Just et al, 1996;Mason and Just, 2007;Newman et al, 2009;Ye and Zhou, 2009), priming (Devauchelle et al, 2009), and violation detection (Ni et al, 2000), it has been suggested that these tasks all involve explicit attentional control (Crinion et al, 2003;Van Petten and Luka, 2006). It is possible that such control processes may interact with semantic unification and constitute an alternative explanation for the LIFG activations observed in these studies.…”
Section: Introductionmentioning
confidence: 99%